Trabalho, direitos coletivos e os princípios da liberdade e da autonomia sindicais: entre o justo e o injusto nas políticas, nas leis e nos tribunais trabalhistas - Cleidimar Rodrigues de Sousa Lima (2015)
This Thesis aims to historicize and analyze the trajectory that has been developed in Ceará State with SINTRO- Workers Union in the State of Ceará Road Transport in the period 1980-2003, with respect to judicial processes has been processed in the Judiciary, more specifically the Regional Labor Court - 7th Region, which sought to notice how this Justice Specialized mediated disputes between employers and their employees in this area; mediated by their unions constituted legally, in which the principles of freedom and union autonomy and dignity of the human person could be enjoyed under the aegis of the dictates of national and international guarantees of the Collective Labour Law. The result of academic investigations into cases, minutes and local newspapers as well as the systematic reading of the Journal LTR, national publication containing Doctrine, Jurisprudence and Labour Legislation, in order to understand the legal ideology in the country within our historical period; the study came from the following questions: How do the regulatory norms of trade union activities in Brazil trade union rights respond achieved and fetched? How the workers of our country use the trade union protection in their conflicts with the employer, more specifically those of the SINTRO-CE? How do the Labor Justice act in these conflicts, when it comes to the application of the jurisdictional provision of standards and principles? And how collective bargaining has been used in these areas? The research has enabled us to understand the multiple ways that led to this Union worker category using this Specialized Justice aiming at the maintenance of their labour rights and Trade Union struggle for the expansion of the same, without fear of dismissal or retaliation. We found that the most more present claims were of salary increase and better working conditions, arguing the workday and their ranges. And that the employer class doesn't always receive with "good eyes" working-class claims, creating a labor disharmony climate only attenuated by State-judge´s intervention represented in the country by the Labour Courts.